Development of an Enhanced Remote Monitoring System of Diesel Levels in Telecom Base Stations - Agesin Ademola Kazeem; Abdulkadir Abubakar; Aliyu Umar Abubakar; Nasiru Abdulsalam; Jamilu Bala Hamza; Zahraddeen Lawan Sani (Darul Yasin Al Sys, 2026)
This study presents the design and implementation of an enhanced Internet of Things (IoT)-based remote monitoring system for managing diesel levels and voltage status in telecommunication base stations (TBSs) to improve operational reliability and reduce fuel-related inefficiencies. A prototype system was developed by integrating ultrasonic fuel-level and voltage sensors with an Arduino Nano microcontroller and an ESP8266 Wi-Fi module. The system transmitted data to a cloud-based IoT platform for real-time visualization and automated alert generation, enabling continuous monitoring and timely notification of critical operating conditions. The system was evaluated in terms of efficiency, reliability, and cost performance under varying load conditions. The results demonstrated a 24.6% increase in monitoring efficiency, a 31% reduction in generator downtime, and an 18% reduction in operational costs compared with manual monitoring methods. These findings indicate that the proposed system offers a scalable, cost-effective, and energy-efficient solution for enhancing transparency, reducing manual oversight, and supporting more sustainable power management in telecommunication base stations. The study contributes practical evidence on the effectiveness of IoT-enabled monitoring for infrastructure management in energy-dependent telecommunications environments.